Sem Asas, Só Penas: Uma Leitura De O Galo De Ouro, De Raquel De Queirós, Comparado A Suas Crônicas - Lima, Jacqueline Nunes De [UNIFESP] (2017)
This Masters dissertation results from a research about the work of Rachel de Queiroz, more exactly her novel O galo de ouro and four short stories: ―Mimiro‖, ―A dor de amar‖, ―Bilhete ao meu leitor de domingo‖ and ―Retrato de um brasileiro‖. This work intends to verify, based on the writer‘s affirmation about the novel O galo de ouro, that these short stories should work as kind of a creative laboratory for the novel itself. The trajectory that was realized counts on a short comment about Rachel de Queiroz‘s literary production, focusing on the short stories and the novel. Next, considering her competence of telling stories, the narrator‘s position and participation are verified and also the kind of speech used. Then an analysis is made about how Rachel de Queiroz represents the poverty in her work which is studied. Based on theoretical support of Roland Barthes that allows to believe that the short stories work like a laboratory for the novel building, showing, after all, which likeness exist between the four short stories chosen and the novel O galo de ouro, proving that they are found in both works, concerning to the characters construction, themes and narrative means, for example.